Brand Origin Recognition Accuracy: Perspectives from Emerging Markets - (:unkn) unknown (INT MANAGEMENT DEVELOPMENT ASSOC-IMDA, 2007)
This research measures and tests a concept referred to as brand origin recognition accuracy (BORA - cf. Samiee, Shimp, Sharma 2005) in the emerging market of Turkey. We explore consumers' knowledge of brand origins based on the model advanced by Samiee et al. (2005) using a small judgment sample of managers and junior managers attending a master's program at one of Turkey's premier graduate schools in Istanbul completed a structured, self-administered questionnaire. These individuals were then enlisted by to researchers in creating a respondent-driven snowball sampling design. Research has demonstrated that snowball samples are well suited to make estimates about social networks (Salganik and Heckathorn 2004), such as networks of managers in a particular industry. We asked the respondents to identify colleagues in their firms who held positions of managers, assistant managers, or managers-in-training, and to ask them to complete the self-administered questionnaires.